2013
DOI: 10.1371/journal.pone.0074727
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Fate of Phenotypic Plasticity and Functional Traits under Domestication in Manioc: Changes in Stem Biomechanics and the Appearance of Stem Brittleness

Abstract: Domestication can influence many functional traits in plants, from overall life-history and growth form to wood density and cell wall ultrastructure. Such changes can increase fitness of the domesticate in agricultural environments but may negatively affect survival in the wild. We studied effects of domestication on stem biomechanics in manioc by comparing domesticated and ancestral wild taxa from two different regions of greater Amazonia. We compared mechanical properties, tissue organisation and wood charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…The direction and magnitude of a plastic response is itself expected to vary from one genotype or population to another and thus be susceptible to alteration through adaptive selection; empirical evidence supports this prediction (Des Marais et al, 2013; Schlichting and Wund, 2014). One aspect of the domestication syndrome in grains appears to be general reduction in plasticity, including the reduction in opportunistic branching achieved in many crops through increased apical dominance and the fixation of dwarfing mutations and other genes that suppress the ability of densely spaced grain plants to manifest the shade‐avoidance response (Ménard et al, 2013). The major maize domestication allele tb1 is less environmentally plastic in its effects than the teosinte allele, and thus makes plants less responsive to changes in plant density (Doebley et al, 1995).…”
Section: Trade‐offsmentioning
confidence: 52%
“…The direction and magnitude of a plastic response is itself expected to vary from one genotype or population to another and thus be susceptible to alteration through adaptive selection; empirical evidence supports this prediction (Des Marais et al, 2013; Schlichting and Wund, 2014). One aspect of the domestication syndrome in grains appears to be general reduction in plasticity, including the reduction in opportunistic branching achieved in many crops through increased apical dominance and the fixation of dwarfing mutations and other genes that suppress the ability of densely spaced grain plants to manifest the shade‐avoidance response (Ménard et al, 2013). The major maize domestication allele tb1 is less environmentally plastic in its effects than the teosinte allele, and thus makes plants less responsive to changes in plant density (Doebley et al, 1995).…”
Section: Trade‐offsmentioning
confidence: 52%
“…Subsequently in Amazonia, detoxification and cultivation techniques were innovated and led to the relaxation of selective pressures against cyanogenic glucosides to the point where a more toxic, but high starch-yielder evolved (66). Recent research has identified traits that facilitate vegetative propagation of cropped manioc, such as pronounced parenchymatous swellings at the nodes leading to brittle stems that can be readily broken for replanting, are absent in wild relatives (67).…”
Section: Comparing Timing Of Domestication In Vegecultural Cropsmentioning
confidence: 99%
“…This is true despite well-grounded research showing strong correlations among organ size (e.g., fruit size), branching intensity, and other domestication syndrome traits [27,34]. Research on allometry, anatomy, or plant hydraulics [35,36] should be implemented to identify and understand constraints in trait evolution during domestication [37]. Other perspectives include trait coordination within the phenotypic space [38,39], quantification of the intensities of phenotypic integration and plasticity [40][41][42], or modeling trait interactions through path analyses [31].…”
Section: Constraints and The Integrated Plant Phenotypementioning
confidence: 99%